SOCIALIZED ACCOUNTS (II). - Littleton, A. C. (The Accounting Review, 1934)
Abstract The British were the first to face the problem of finding a way to control unsocial individualism without resorting to absolute prohibitions. Early in the nineteenth century the government was under pressure to relax the prohibition of company promotion which dated from 1720 and to make the incorporation of joint stock companies somewhat easier. But the thought of simple repeal of the Bubble Act brought visions of another disastrous era of unrestrained stockjobbing and wild speculation. The problem was to find a way to yield to the pressure for free incorporation without opening the way for former excesses. The answer was found in breaking the privacy of accounting information. This was the British approach in the early nineteenth century to a control over private business affairs through semi-public accounts. Attempts at control in the United States came later and seem in comparison rather unorganized. The U.S. have had nothing quite as effective as the British registration of proposed incorporations.